2001
DOI: 10.1086/319566
|View full text |Cite
|
Sign up to set email alerts
|

Individual Wealth, Reservation Wages, and Transitions into Employment

Abstract: We investigate the relationship between financial wealth, reservation wages, and labor market transitions. Wealth is assumed to affect the level of the reservation wage and the employment probability. We test for the validity of this assumption by estimating a simultaneousequations model of reservation wages, labor market transitions, and wealth. The data used for the analysis relate to a sample of unemployed job searchers. We use subjective information on the reservation wage. Wealth is found to have a signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
100
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(109 citation statements)
references
References 17 publications
7
100
0
2
Order By: Relevance
“…First, the literature on job offer acceptance is often based on the concept of a reservation wage, which permits empirical predictions concerning the duration of unemployment in relation to the number of available jobs and their wage level. These proposed relationships have been tested and confirmed extensively on an empirical level (Addison et al 2010;Bloemen and Stancanelli 2001; for an overview, see LudwigMayerhofer 2008a: 218 et seq.). One drawback of this approach has been that the separation of supply-and demandside factors was barely feasible or only possible indirectly 4 For monetary job characteristics, a similar argument could be made.…”
Section: Literature Reviewmentioning
confidence: 81%
“…First, the literature on job offer acceptance is often based on the concept of a reservation wage, which permits empirical predictions concerning the duration of unemployment in relation to the number of available jobs and their wage level. These proposed relationships have been tested and confirmed extensively on an empirical level (Addison et al 2010;Bloemen and Stancanelli 2001; for an overview, see LudwigMayerhofer 2008a: 218 et seq.). One drawback of this approach has been that the separation of supply-and demandside factors was barely feasible or only possible indirectly 4 For monetary job characteristics, a similar argument could be made.…”
Section: Literature Reviewmentioning
confidence: 81%
“…They calculate hourly reservation wages using wage information from the Longitudinal Retirement History Survey (LRHS). Bloemen and Stancanelli (2001) reservation wages that are constant over the duration of nonemployment. Information concerning reservation wages is not always included for every country and every year.…”
Section: Previous Empirical Findingsmentioning
confidence: 99%
“…For example, a recent study by Bloemen and Stancanelli (2001) uses self-reported reservation wages for unemployed workers in the Dutch socio-economic panel from 1987 to 1990. They report in their Table 4 that a 1000 Florin increase in unemployment income raises the reservation wage of household heads by 4.4 percent and of spouses by 9.0 percent, although the latter figure is not statistically different from zero.…”
Section: Measurementmentioning
confidence: 99%
“…This is not necessarily equal to the average value ofw n b among unemployed workers, the quantity that Feldstein and Poterba (1984) and Bloemen and Stancanelli (2001) measure using self-reported reservation wages.…”
Section: Worker Heterogeneitymentioning
confidence: 99%